Effects of obesity on gait pattern in young individuals with Down syndrome. Issue 1 (March 2015) - Galli, Manuela; Cimolin, Veronica; Rigoldi, Chiara; Condoluci, Claudia; Albertini, Giorgio
<x xml:space="preserve">Abstract</x> In individuals with Down syndrome (DS), the prevalence of obesity is widespread; despite this, there are no experimental studies on the effect of obesity on gait strategy in DS individuals. The aim of this study is to assess the clinical gait analysis of a group of obese individuals with DS and a group of nonobese individuals with DS to determine whether obesity produces a different gait pattern in these participants. In addition, although females and males share a similar mass, they are characterized by different fat distribution and/or accumulation; thus, the presence of differences between females and males within the two DS groups was investigated. Gait analysis data of a group of 78 young individuals with DS and 20 normal-weight participants in the 5–18-year age range were considered. Among DS individuals, 40 were classified as obese (obese DS group), whereas 38 were classified as normal weight (nonobese groups). A three-dimensional gait analysis was carried out using an optoelectronic system, force platforms and video recording. Spatiotemporal, kinematic and kinetic parameters were identified and calculated for each participant. Our results show that most of the parameters were similar in the two groups of DS participants; the only differences were in terms of stance duration, longer in the obese DS group and dorsiflexion ability during the swing phase, which was limited in the obese DS group. The two DS groups were significantly different in terms of ankle stiffness (Ka index): both groups were characterized by reduced values compared with the control group, but the obese group presented lower values with respect to nonobese participants. The data showed that females were characterized by significant modifications of gait pattern compared with males in both groups, in particular, at proximal levels, such as the hip and the pelvis. Our findings indicate that the presence of obesity exerts effects on gait pattern in DS individuals and in particular on ankle joint stiffness. These results may have special clinical relevance; the biomechanical comparison of gait in young obese and nonobese DS individuals may provide a basis for developing either specific or common rehabilitative strategies.